Characteristics of Cutaneous Lupus Erythematosus Patients in Dermatology and Venereology Outpatient Clinic - Suryawati, Nyoman; Praharsini, I Gusti Ayu Agung; Elis Indira, I Gusti Ayu Agung; Darmaputra, I Gusti Nyoman (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Cutaneous lupus erythematosus (CLE) is a specific skin manifestation of lupus erythematosus. This condition can be accompanied by systemic involvement that affect patient therapy and prognosis. The characteristics of CLE patients in Indonesia have not been widely reported. This study aims to determine the prevalence and characteristics of CLE patients at Dermatology and Venereology Outpatient Clinic of Allergy and Immunology Division at Ngoerah Hospital. Methods: This research used descriptive analysis with a cross-sectional design and total sampling method. Result: The total number of patients was 34, with prevalence of 6.7 cases per 1,000 patients. The majority of patients were female (85.3%), Balinese ethnicity (70.6%), unemployed (53%), with a high school/vocational high school education (56%), and risk factors of sun exposure (80.0%). Most patients had no family history of Lupus erythematosus (LE) (65.7%). The most frequent skin manifestation was chronic type CLE (28.6%). Based on The European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) score, 27 patients (77.1%) met Systemic lupus erythematosus (SLE) criteria. Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) activity, damage, and Mexican Systemic Lupus Erythematosus Disease Activity (MEX-SLEDAI) scores were 3.35±4.52, 0.88±1.96, and 7.5±5.09. Systemic therapy included methylprednisolone (47%) and hydroxychloroquine (35.2%), topical treatment included high to very high-potency steroids (67.6%), and sunscreen (14.7%). Response therapy was generally good in 68.6% of patients. Conclusion: The most common type of CLE is chronic cutaneous lupus erythematosus. Most patients improved, with the majority using systemic methylprednisolone and topical high-potency corticosteroids. Oral treatment responses tend to be good.